Mentalizing Self and Other and Affect Regulation Patterns in Anorexia and Depression - Rothschild-Yakar, Lily; Stein, Daniel; Goshen, Dor; Shoval, Gal; Yacobi, Assaf; Eger, Gilad; Kartin, Bar; Gur, Eitan (Frontiers in Psychology, 2019)
The aim of this study was to assess general mentalizing processes and the specific component of affective mentalizing regarding self and others alongside affect regulation patterns in female adolescent and young adult inpatients with anorexia nervosa (AN; n=41), depression (n=20) and controls (n=53). For this purpose, we used tools assessing reflective functioning (RF), complex emotion recognition and theory of mind (ToM), alexithymia, affect regulation, depression, and eating-disorder (ED) symptoms. The AN and depression groups exhibited lower general mentalizing and higher alexithymia, emotional reactivity, and emotional cutoff patterns than controls, but showed no greater disturbance in ToM. The two clinical groups did not differ on any of these variables. Elevated mentalizing and adequate affect regulation patterns separately predicted lower severity of ED symptoms. Nonetheless, affect regulation did not add to the predictive value of mentalizing variables. Specifically, elevated alexithymia, and depressive symptomatology, but not RF, predicted greater ED symptomatology. Moreover, alexithymia directly accounted for elevated ED symptoms and also indirectly connected with ED symptoms via emotional hyperactivation and elevated depressive symptoms. These findings suggest that deficiencies in menetization and affect regulation are not unique to AN, but may rather associated with psychopathology in general. Nonetheless, alexithymia and depression may increase ED-related symptomatology. Affect regulation deficiencies are mainly related with depressive symptoms and emotional hyperactivation is indirectly related with AN via the depressive symptoms.